Level of tumor-infiltrating lymphocytes and PD status as potential prognostic markers of survival and therapy effectiveness in triple-negative breast cancer - A. F. Nasretdinov; N. I. Sultanbaeva; Sh. I. Musin; A. V. Pushkarev; K. V. Menshikov; V. A. Pushkarev; A. V. Sultanbaev (Опухоли женской репродуктивной системы)
In breast cancer, genetic profile and expression of immunohistochemical markers determine prognosis and treatment scheme. Triple-negative breast cancer is characterized by absence of hormone receptor expression and negative HER2 status, as well as high proliferative index. These features of the tumor tissue limit doctors» selection of antitumor drugs. Development of triple-negative variant of tumor tissue is associated with a mutation in the BRCA1/2 gene. Consequently, determination of BRCA1/2 mutations is a prognostic biomarker, and in triple-negative cancer presence of expression of immune checkpoint proteins, multiprotein receptors on the surface of immune cells and tumor tissue play an important role in prognosis and selection of treatment strategy. Additionally, some studies demonstrate existence of multiple prognostic markers which allow to divide patients with triple-negative breast cancer into subgroups facilitating prognosis and selection of treatment strategy.